DISTRIBUSI DAN IDENTIFIKASI POPULASI SINTRONG (Crossocephalum crepidiodes.Benth) RESISTEN PARAKUAT PADA LAHAN JAGUNG (Zea mays) DI KABUPATEN DAIRI - Sianturi, Berton (Jurnal Online Pertanian Tropik, 2017)
Crassocephalum crepidioides on Cornfields in Dairi Regency had been reported to become more difficult to control using paraquat. The objective of the research was to determine the characteristics and the distribution of C.crepidioides resistant to paraquat in cornfields. The experiment was carried out in two steps, the first step was screening the population of C. crepidioides with paraquat at the recommended dose, and the second step, dose-response experiment for the resistance level of C. crepidioides population with dose 0, 76, 152, 304,5, 609, 1218, and 2436 g.ai /ha. In the first step experiment, paraquat dichloride was applied at 280 g.ai/ha. The treatments were arranged in a randomized block design with 3 replication. The second step experiment was that the resistant populations confirmed in the first experiment were sprayed for their dose-response. The treatments were arranged in a randomized complete block design (CRBD). The results showed that of 30 populations of C. crepidiodes, 19 populations (63.3%) were categorized to be resistant with the mortality ranging from 10.84% to 52.08%, and 11 populations (36.7%), was categorized as high resistance with mortality of 0% to 9.21%. The level of resistance (R/S) of R-C25, R-C27, and R-C30 populations of C. crepidioides were 12,3, 14,86, and 24,83 times consecutively, compared with the susceptible population. The number of C. crepidioides chlorophyl leaves in susceptible populations was significantly lower than that of a resistant populations.